PERAN PERSONALITY TRAITS TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN IMPOSTOR SYNDROME SEBAGAI MEDIATOR PADA KARYAWAN DI JABODETABEK - Thasya Prettycia; Zamralita; Reza Fahlevi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of personality traits on Organizational Citizenship Behavior (OCB) with impostor syndrome as a mediator among employees in Greater Jakarta. A quantitative approach was used on 189 employees through convenience sampling. Data were collected using the Big Five Inventory (BFI), Organizational Citizenship Behavior Checklist 20 Items (OCB-C 20 Items), and Impostor Profile 30 (IPP-30), then analyzed with SPSS using the PROCESS Macro Model 4. The results showed that the average levels of personality traits, OCB, and impostor syndrome were in the high category. All dimensions of personality traits had a significant effect on OCB (p < 0.05), with the neuroticism dimension showing a significant negative result (β = -2.70; p = 0.044). The mediation analysis results showed that impostor syndrome bridged the relationship between the extraversion dimension and OCB (BootCI 95%: -1.55 to -0.08) and the neuroticism dimension and OCB (BootCI 95%: 0.007 to 3.02), while other dimensions showed insignificant results. These findings confirm that personality traits directly drive OCB, and impostor syndrome can mediate the role of personality traits on OCB in individuals with high extraversion and neuroticism.